Automatisation et supervision d’une fardeleuse par l’api siemens S7 1214C - Ferhat Mohammed; Ferhat Islem Farouk; Aboubakeur HADJAISSA (Université Amar Thelidji- Laghouat FACULTE: DE TECHNOLOGIE DEPARTEMENT D’ELECTRONIQUE, 2022)
The work presented in this thesis allows to update the control system of a shrink-wrapper in a production line of carbonated beverages at the factory S.A.R.L MOULAI which is located in the activity zone EL ASSAFIA / LAGHOUAT. A detailed study was conducted on all the actuators and sensors of the system of the shrink-wrapper. We presented the specifications, modeling by GRAFCET and the program that describe the operation of the system using the PLC S 1214C under the environment TIA PORTAL of SIEMENS. We also used the PLCSIM simulator to validate the program described before, and the flexible software WINCC for the design and supervision of the man-machine interface.
OPTION : Electronique des systèmes embarqués